Biodiversity of zooplankton in industrial Hajara lake (Sebha – Libya) - Aisha Arhouma Ali Amer (Journal of Pure & Applied Sciences, 2019)
The taxonomical study of zooplankton in Industrial Hajara lake was studied for the period March - May 2017 occurrence three phyla   namely: Platyhelminthes, Rotifera and Arthropoda. One genus of Platyhelminthes  was recorded in the lake while phylum Rotifera consist of two classes: Bdelloidea and Monogononta. The last one of class Rotifera consider more diversity in the of families which consist of eight families such as Brachionidae (12 species) then Lancanidae (3 species). Arthropoda represent to class Crustacea are more diversity which belonge to three classes:  Branchiopoda,   Ostracoda and  Copopoda.